The global housing affordability crisis: Policy options and strategies - Albert Saiz (Institute of Labor Economics (IZA), 2023)
Housing prices are rising faster than incomes in many areas of the world, reducing wellbeing and engendering social discontent. Passivity by municipal and national governments is no longer an option. In this essay, I will describe the tradeoffs between different housing policy objectives of governments and the public. I suggest that policy goals should be made explicit, and their tradeoffs acknowledged. Due to the durable impact of real estate development, housing and land-use policies should seek broad inter-partisan consensus. To avoid pernicious general equilibrium effects and because of limited public resources, subsidies ought to be carefully targeted. I will describe the thirty major economic strategies underpinning housing policies worldwide and discuss their main advantages and caveats. Effective housing programs must skillfully deploy a combination of these basic economic strategies, as I will illustrate through several global case studies. Programs should be carefully designed to anticipate behavioral responses from individuals, firms, governments, and markets. Unideological and professional implementation is critical for their success.
Keywords: H53; I38; R21; R31; 330; real earnings; housing and family income; social policy